1988
DOI: 10.1007/bf01720830
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind placebo controlled trial of diltiazem in duchenne dystrophy

Abstract: The role of calcium accumulation in the pathogenesis of Duchenne muscular dystrophy (DMD) has already been discussed. Several trials with different calcium-blocking drugs have revealed no clinical benefit. In addition, the present study includes histological investigations and computer tomography to verify therapeutic effects. In a randomized placebo-controlled double-blind study, 13 DMD patients aged from 3-10 years (mean, 7 years) were treated with 5 mg/kg diltiazem daily for 1 year. Compared with before the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
2

Year Published

1990
1990
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 15 publications
0
12
0
2
Order By: Relevance
“…In addition, basal activities of Ca 2+ ‐selective leak channels have been reported to be significantly elevated in dystrophin‐deficient myotubes or dystrophic skeletal muscle fibers,17 and this may explain the increased calcium concentration in mdx fibers seen in the present study. The plasma emission spectrometry technique used here seems to be a valuable tool for the evaluation of overall changes in calcium as a result of drug therapy or other experimental conditions,53 and the results may be best compared to those obtained for DMD patients, in whom muscle biopsies are taken for the determination of muscle calcium content 5, 35. In DMD, muscle Ca 2+ was not found to be affected by diltiazem 5.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In addition, basal activities of Ca 2+ ‐selective leak channels have been reported to be significantly elevated in dystrophin‐deficient myotubes or dystrophic skeletal muscle fibers,17 and this may explain the increased calcium concentration in mdx fibers seen in the present study. The plasma emission spectrometry technique used here seems to be a valuable tool for the evaluation of overall changes in calcium as a result of drug therapy or other experimental conditions,53 and the results may be best compared to those obtained for DMD patients, in whom muscle biopsies are taken for the determination of muscle calcium content 5, 35. In DMD, muscle Ca 2+ was not found to be affected by diltiazem 5.…”
Section: Discussionmentioning
confidence: 92%
“…Several studies have investigated the use of diltiazem for the treatment of DMD. Although these studies indicated some positive effects of diltiazem, there were no statistically significant data supporting its treatment efficacy 5, 29, 35. In a hamster model of dystrophy, diltiazem was found to be effective in protecting against muscle degeneration 25, 27.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It has already been shown that the Ca2+ entry blocker, diltiazem, alleviates the symptoms presented by a cardiomyopathic hamster model (Johnson & Bhattacharya, 1993). This compound also has a slight beneficial effect in DMD patients (Bertorini et al, 1988) although no effect was found in another clinical study (Pernice et al, 1988). The mechanism involved in PDN-triggered reduction in…”
Section: Discussionmentioning
confidence: 97%
“…Serum enzymes such as creatine kinase (CK), creatine kinase MB (CK-MB), aldolase (ALD), and lactate dehydrogenase (LDH) present increased activity under DMD conditions during the first three years of life, which indicates muscular degeneration (Pernice et al, 1988). The activity of these muscle enzymes is important for the diagnosis of muscular diseases.…”
Section: Introductionmentioning
confidence: 99%